Impact of electronic commerce on consumer behaviour and attitude in Singapore. - Seah, Judy Bee Woon. (2008)
This paper studied the impact of e-commerce on consumer behaviour and attitude in Singapore to add to the existing knowledge about the online market. The profile of an online shopper, factors encouraging or discouraging online shopping as well as attitudes towards e-commerce as a whole are explored.